Comparison of the 2-D Dose Distribution Calculated by Planning System and Measured by Gafchromic Film Physical Dosimetry for 60Co and 192Ir Brachytherapy Sources - M H Gholami; M Sadeghi; F Babapour Mofrad; M Mohammadi (Journal of Biomedical Physics and Engineering, 2020)
Background: High Dose Rate (HDR) brachytherapy sources with high photon energy have been widely used in treating tumors. Dosimetric parameter of these brachytherapy sources should be determined according to the AAPM TG-43 recommendation. Gafchoromic films are reliable tools for this evaluation. Objective: The aim of this study is to evaluate and compare dose accuracy of the two-brachytherapy sources in a dedicated phantom. Material and Methods: In this analytical study, two common sources, including Cobalt and Iridium, were loaded into the dedicated phantom. The two-dimensional dose distribution around the source was calculated by TPS system for certain activities and geometries around the sources. Then, the experimental dose measured by Gafchromic film dosimetry was reported for different angles ranging from 0 to 180 degrees. Results: The difference between calculated and measured doses was less than 6 percent (-5 to +6 percent) for all of the channels and angles. These errors are smaller and mainly more than zero (Dfilm>DTPS) for angles less than 20 and larger than 110 degrees. There is no statistically significant discrepancy in dose calculation by treatment planning system. Conclusion: Although the estimated error in dose calculation is not significant, there is still an opportunity to increase the treatment precision. The correlation between the error and the angle should be considered in further plans of brachytherapy. The present study showed comparable errors compared to results of other research studies.